Pengaruh Brand Awareness, Brand Image, Promosi Digital dan Gaya Hidup Terhadap Keputusan Pembelian Iphone : Studi Kasus Mahasiswa FEB Universitas Labuhanbatu - Suri Kholiza; Marlina Siregar; Praida Hansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of brand awareness (X1), brand image (X2), digital promotion (X3), and lifestyle (X4) on iPhone purchasing decisions (Y) case study of FEB Labuhanbatu University Students. The type of research used is descriptive research with a quantitative approach. The sample used was 91 respondents who were Labuhanbatu University Students using purposive sampling technique based on the slovin formula. Data collection was carried out by distributing questionnaires via google forms online to FEB Labuhanbatu University Students. The data analysis method was carried out through instrument testing, classical assumption testing, multiple regression analysis and hypothesis testing using the statistical package for the social sciences (SPSS). The results of this study indicate that the brand awareness variable has a positive and significant effect on iPhone purchasing decisions, brand image has a positive and significant effect on iPhone purchasing decisions, digital promotion has a positive and significant effect on iPhone purchasing decisions, lifestyle has a positive and significant effect on iPhone purchasing decisions.